2014
DOI: 10.1111/epi.12801
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to treatment causing acute hospitalizations in people with epilepsy: An observational, prospective study

Abstract: Summary The aim was to assess the clinical relevance of antiepileptic drug (AED) nonadherence by means of therapeutic drug concentration monitoring (TDM). Two hundred eighty‐two consecutive patients with epilepsy acutely admitted to hospital for seizures were included. Nonadherence was defined as having a serum concentration/dose ratio at admission of <75% of the patient's own control value (probable nonadherence: 50–75%; definite: <50%). Nonadherence was identified in 39% of patients (definite 24%; probable 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 13 publications
(32 reference statements)
4
57
2
3
Order By: Relevance
“…This finding is similar to the results reported by Gabr and Shams, (17) but differs from the results of Kyngäs' study, which showed that a duration of epilepsy > 3 years was significantly related to adherence to medications. (18) However, a significant association between generalised epilepsy and nonadherence to AED was found in the present study, as well as in the study by Samsonsen et al; (19) the reason for this observation is elusive. One possible explanation that may account for the higher rate of adherence is that episodes of focal epilepsy are more frequent than generalised epilepsy.…”
Section: Discussionsupporting
confidence: 50%
“…This finding is similar to the results reported by Gabr and Shams, (17) but differs from the results of Kyngäs' study, which showed that a duration of epilepsy > 3 years was significantly related to adherence to medications. (18) However, a significant association between generalised epilepsy and nonadherence to AED was found in the present study, as well as in the study by Samsonsen et al; (19) the reason for this observation is elusive. One possible explanation that may account for the higher rate of adherence is that episodes of focal epilepsy are more frequent than generalised epilepsy.…”
Section: Discussionsupporting
confidence: 50%
“…In patients using AEDs at admission, serum concentrations were drawn in the emergency room and compared with drug-fasting steady state controls. Definite non-adherence was defined as a concentration/dose ratio on admission of 50% or lower compared to the control ratio (Samsonsen et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…p-piller) er viktig. Mange gjennombruddsanfall skyldes at pasienten har glemt å ta medisinene (42). Dette kan unngås ved for eksempel bruk av medisindosett og alarm på mobilen på tidspunkter for medisininntak.…”
Section: Forebyggende Tiltakunclassified